Control and Insecurity in Australian and Canadian Universities during the COVID-19 Pandemic - Peetz, David; O’Brady, Sean; Weststar, Johanna; Coles, Amanda; Baird, Marian; Cooper, Rae; Charlesworth, Sara; Pyman, Amanda; Ressia, Susan; Strachan, Glenda; Troup, Carolyn (Relations industrielles / Industrial Relations, 2022)
SummaryThis study examines how the COVID-19 pandemic and ensuing university management control strategies have influenced higher education workers’ job security, stress and happiness. The primary quantitative and qualitative data are drawn from a survey of fourteen universities across Australia and Canada, supplemented by secondary research. The analysis examines institutional and worker responses to the pandemic, and resulting conflict over financial control at the macro (sector), meso (university) and micro (individual) levels.At the macro level, university responses were shaped by public policy decisions at both national and subnational layers of the state, and the higher education sector in both countries had a distinctly neoliberal form. However, Australian universities were exposed to greater financial pressure to cut job positions, and Australian university management might have been more inclined to do so than Canadian universities overall. Different institutional support for unionism at the macro level influenced how university staff were affected at the meso and micro levels. Restructuring at the universities across both countries negatively impacted job security and career prospects, in turn leading to reduced job satisfaction and increased stress. Although working from home was novel and liberating for many professional staff, it was a negative experience for many academic staff.Our analysis demonstrates that the experiences of university staff were influenced by more than the work arrangements implemented by universities during the COVID-19 pandemic. The approaches of universities to job protection, restructuring and engagement with staff through unions appeared to influence staff satisfaction, stress and happiness.Our findings extend the literature that documents how university staff routinely challenge neoliberalization processes in a variety of individual and collective actions, particularly in times of crisis. We argue that theorization of struggles over control of labour should be extended to account for struggles over control of finance.AbstractWe studied 14 universities across Canada and Australia to examine how the COVID-19 crisis, mediated through management strategies and conflict over financial control in higher education, influenced workers’ job security and affective outcomes like stress and happiness. The countries differed in their institutional frameworks, their union density, their embeddedness in neoliberalism and their negotiation patterns. Management strategies also differed between universities. Employee outcomes were influenced by differences in union involvement. Labour cost reductions negotiated with unions could improve financial outcomes, but, even in a crisis, management might not be willing to forego absolute control over finance, and it was not the depth of the crisis that shaped management decisions.